(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article conducts a comprehensive study of the “Tashkent period” by doctor, professor Khalel Dosmukhameduly (1883 – 1939). His selfless work in the organization of Kazakh science, as a publisher-editor, and most importantly, his significant research in the field of linguistics as a Turkologist is analyzed. H.Dosmukhameduly, who left an indelible mark on Kazakhstani science for several years, is a phenomenon, therefore the development of his heritage is a requirement of modernity. For 60 years in Kazakhstan from 1929 to the beginning of 1989, the official Soviet-communist system did not allow to name not only Khalel Dosmukhameduly, but also hundreds of so-called “Alash” Kazakh experts: none of their works (articles, books) were published; even the materials that studied them did not pass the censorship filter; the absence of any understanding of them in the memory of the people was strictly observed; in fact, their names, social activities and personal creations have become a “blank spot” in the history of the country. Investigating the fate of the Alash Kazakh readers at the beginning of the 20th century, and in order to familiarize themselves with the written materials stored only in the secret funds of the archives (the so-called “special depository”), they first had to master the Arabic script (kadym and zhadit). We can say that the last thirty years of our life have passed on this difficult creative path: we had to find as much of the scientific and journalistic heritage of our scientists Akhmet Baitursynuly and Halel Dosmukhameduly as possible, translate their works into modern Cyrillic and publish them in volumes. In fact, this is a complex text work that requires diligence to meet the social needs of the new Kazakhstan. After collecting a complete database of books and articles by A. Baitursynuly and H. Dosmukhameduly, written and published in Arabic script at the beginning of the 20th century, multi-volume works about their lives and destinies, socio-political views and ways of struggle were published in large numbers and distributed among the people. Our goal was to write and present the results of a study of his work. The article presented is one of the first studies with this purpose. Key words: linguistic personality, Turkology, history of language, harmony, vowel harmony.